Efektivitas Program Keluarga Harapan (PKH) Dalam Upaya Mengurangi Beban Pengeluaran Keluarga Miskin Di Nagori Kandangan Kecamatan Pematang Bandar Kabupaten Simalungun - Ananda Dwi Arum; Tunggul Sihombing (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
The Family Hope Program (PKH) is a conditional social assistance provided to poor families with components of health (toddlers and pregnant women), education (elementary, junior high, and high school children), and social welfare (elderly and socially disabled). This study aims to determine and describe the effectiveness of the Family Hope Program (PKH) in an effort to reduce the burden of spending on poor families in Nagori Kandangan, Pematang Bandar District, Simalungun Regency. The research method used is a descriptive method with a qualitative approach. Data collection techniques were carried out by interview, observation, and documentation. The results showed that PKH in Nagori Kandangan is still not effective. In terms of achieving goals, there are still delays in the distribution of PKH funds and the inaccuracy of PKH targets. In integration indicators, PKH is still not fully integrated and there is still a lack of understanding of KPM related to PKH due to the lack of socialization held. In the adaptation dimension, PKH is still not able to adapt to the wishes of KPM, especially in opening a business.